Molecular Investigations of Two First Brucella suis Biovar 2 Infections Cases in French Dogs - Guillaume Girault; Vitomir Djokic; Fathia Petot-Bottin; Ludivine Perrot; Bourgoin Thibaut; Hoffmann Sébastien; Acacia Ferreira Vicente; Claire Ponsart; Luca Freddi (Pathogens, 2023)
Despite Brucella suis biovar 2’s (BSB2) active circulation in wildlife, no canine infections have been reported. The present paper is the first to describe two cases of BSB2 infections in French dogs. The first case occurred in 2020 and concerned a 13-year-old male neutered Border Collie with clinical signs of prostatitis. The urine culture revealed the excretion of significant levels of Brucella in the sample. The second case concerned a German Shepherd with bilateral orchitis, in which it was possible to detect Brucella colonies following neutering. HRM-PCR and classical biotyping methods classified both isolated strains as BSB2, in contrast to expected B. canis, which is usually the etiological agent of canine brucellosis in Europe. The wgSNP and MLVA analyses highlighted the genetic proximity of two isolates to BSB2 strains originating from wildlife. No pig farms were present in the proximity of either dog’s residence, ruling out potential spill over from infected pigs. Nevertheless, the dogs used to take walks in the surrounding forests, where contact with wildlife (i.e., wild boars or hares, or their excrements) was possible. These cases highlight the importance of adopting a One Health approach to control the presence of zoonotic bacteria in wild animals and avoid spillovers into domestic animals and, potentially, humans.